BALANCED SCORECARD DESIGN AS PERFORMANCE MEASUREMENT PT.ESCORINDO - Rahmi, Atika (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2022)
PT. Escorindo is a loading and unloading company that was established in 2000 but there is no performance measurement yet. This study aims to measure performance measurement through the balanced scorecard through a financial perspective. This study uses primary data with good results from a financial perspective at PT. Escorindo. Good customer perspective, good internal and business process perspective, and your learning growth perspective is good.